2009
DOI: 10.1016/j.immuni.2008.10.020
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Adhesion Primes Antigen Receptor-Induced Calcium Responses through a Transient Rise in Adenosine 3′,5′-Cyclic Monophosphate

Abstract: It is well established that sustained increases in cyclic AMP (cAMP) such as those triggered by forskolin inhibit T cell activation. We describe here an unexpected phenomenon: in T cells, a transient cAMP increase triggered by the interaction with a dendritic cell strongly potentiates T cell receptor (TCR) signaling. We discovered this effect by examining the molecular basis of the adhesion-dependent sensitization of T cells. T cell adhesion caused extracellular-signal-regulated kinase (ERK) activation, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 41 publications
1
58
0
1
Order By: Relevance
“…Indeed, the adhesive signal delivered by LFA1 (induced to adopt its high-affinity form through chemokine-dependent signaling) has been shown to be sufficient to induce immunological synapse formation, whereas the TCR signal is important for synapse stabilization and for sustained activation (Contento et al, 2010). In contrast, we have recently reported that T cell adhesion is able to prime the T cell response, regardless of whether integrins were involved (Conche et al, 2009). Finally, T cells have been shown to be able to sense the rigidity of the object with which they interact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the adhesive signal delivered by LFA1 (induced to adopt its high-affinity form through chemokine-dependent signaling) has been shown to be sufficient to induce immunological synapse formation, whereas the TCR signal is important for synapse stabilization and for sustained activation (Contento et al, 2010). In contrast, we have recently reported that T cell adhesion is able to prime the T cell response, regardless of whether integrins were involved (Conche et al, 2009). Finally, T cells have been shown to be able to sense the rigidity of the object with which they interact.…”
Section: Discussionmentioning
confidence: 99%
“…We have excluded the involvement of a Ca 2+ rise. We have recently shown that a very early transient increase in cAMP is triggered in T lymphocytes after contact with APCs (Conche et al, 2009). This cAMP transient could constitute a good candidate for adhesion-induced antisynapse formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Эта модель согласуется с противовоспалительными эффектами cAMP, которые показаны в некоторых других клеточных системах [38,39] и предположением, что ингибирование продукции cAMP должно усиливать Т-клеточный иммунитет. Однако результаты некоторых недавних исследований показали, что продукция cAMP может так же стимулировать Т-клеточный ответ [40].…”
Section: рисунокunclassified
“…In a few cases increased cAMP may even potentiate the T-cell activation signal (15), particularly at early stages of activation. Recent MS-based proteomic studies have been useful in characterizing changes in the phosphoproteome of T cells under various stimuli such as T-cell receptor stimulation (16), prostaglandin signaling (17), and oxidative stress (18), so much of the total Jurkat phosphoproteome is known.…”
mentioning
confidence: 99%